Influence of Leukotriene Pathway Polymorphism on Responsiveness to Montelukast, Budesonide Plus Formoterol in Patients with Asthma - Ali, Hanan J. (PROSPECTIVE RESEARCHES, 2024)
Variability between patients in response to montelukast, and budesonide / formoterol inhalation powder may be related to genetic variation and non-genetic factors. this paper aims to determine association between polymorphism in leukotriene pathway candidate gene with lung function outcomes in Iraqi patients with asthma receiving montelukast, budesonide plus formoterol inhaler in comparison with healthy control. This research was done on a study group of 80 Baghdad-based Iraqi patients. 40 asthmatic patients receiving montelukast were in the first group, while 40 asthmatic patients on budesonide / formoterol inhalation powder (160/4.5mcg/dose) were in the second group. Screening for the presence of ALOX5 rs2115819, LTA4H rs2660845 and CysLTR1 rs320995 SNPs allelic variants genes were determined using conventional PCR technique and sequencing. In montelukast group, the % change in FEV1 in patients with the GG genotype for ALOX5 (rs2115819) SNP were significantly improved after montelukast intake compared with those carrying AA or AG genotypes. For budesonide / formoterol inhalation powder patients group, the included polymorphism had no significant association with the %change in FEV1. As a conclusion Asthmatic patients carrying AA genotype for ALOX5 rs2115819 may not achieved the optimal response to montelukast treatment. Budesonide / formoterol inhalation powder cannot be used effectively in patients with ALOX5 rs2115819 polymorphism.